Does collaboration among participants lead to better ideas in IT-based idea competitions? An empirical investigation. (9th September 2011) - Blohm, Ivo; Bretschneider, Ulrich; Leimeister, Jan Marco; Krcmar, Helmut
Open innovation research shows that idea competitions are a promising approach for integrating customers and that most innovations are a result of intensive collaboration (Franke and Shah, 2003; Gascó-Hernández and Torres-Coronas, 2004; Nemiro, 2001; Sawhney et al., 2005). Thus, fostering collaboration among idea contributors might be a fruitful approach for unleashing the customers' entire creative potential and making idea competitions even more successful. This paper reports on a field study in which idea contributors could collaborate in an IT-based idea competition using the wiki technology. We tested whether user collaboration positively influences the quality of the submissions applying an in-depth analysis of idea quality. Our results show that user collaboration enhances idea quality and that inducing user collaboration is a viable design element for making idea competitions more effective. This contributes to a more successful design, implementation and operation of idea competitions, as well as to better outcomes. The article concludes with a discussion of customer groups collaborating in idea competitions (extrinsically and intrinsically motivated customers).